2022
DOI: 10.1021/acsphotonics.2c00330
|View full text |Cite
|
Sign up to set email alerts
|

Tapered Optical Fibers Coated with Rare-Earth Complexes for Quantum Applications

Abstract: Crystals and fibers doped with rare-earth (RE) ions provide the basis for most of today’s solid-state optical systems, from lasers and telecom devices to emerging potential quantum applications such as quantum memories and optical to microwave conversion. The two platforms, doped crystals and doped fibers, seem mutually exclusive, each having its own strengths and limitations, the former providing high homogeneity and coherence and the latter offering the advantages of robust optical waveguides. Here we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It would be also interesting to study Yb 3+ and Er 3+ complexes that emit in the near-infra-red region because such complexes are useful for realizing molecule-based quantum communication architectures. , Two recent reports elucidate narrow optical linewidths associated with Yb 3+ complexes, , implying the utility of Ln 3+ complexes for creating coherent light–matter interfaces with quantum technological implications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It would be also interesting to study Yb 3+ and Er 3+ complexes that emit in the near-infra-red region because such complexes are useful for realizing molecule-based quantum communication architectures. , Two recent reports elucidate narrow optical linewidths associated with Yb 3+ complexes, , implying the utility of Ln 3+ complexes for creating coherent light–matter interfaces with quantum technological implications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The efficient emission of Er 3+ at 1550 nm improves data transmission in the C-band (1530 and 1565 nm) [202,203]. It was shown that tapered optical fibres coated with rare earth complexes could find quantum applications [204]. Lanthanoids also have a fundamental role in lasers.…”
Section: Luminescencementioning
confidence: 99%